Various forms of double burden of malnutrition problems exist in rural Kenya - Fongar, A.; Gödecke, T.; Qaim, M. (Springer, 2019)
Background: The coexistence of overweight/obesity and undernutrition is often referred to as the double burden of malnutrition (DB). DB was shown to exist in many developing countries, especially in urban areas. Much less is known about DB in rural areas of developing countries. Also, the exact definition of DB varies between studies, making comparison difficult. The objective of this study is to analyse DB problems in rural Kenya, using and comparing different DB definitions and measurement approaches. Methods: Food intake and anthropometric data were collected from 874 male and female adults and 184 children (<5 years) through a cross-section survey in rural areas of Western Kenya. DB at the individual level is defined as a person suffering simultaneously from overweight/obesity and micronutrient deficiency or stunting. DB at the household level is defined as an overweight/obese adult and an undernourished child living in the same household, using underweight, stunting, wasting, and micronutrient deficiency as indicators of child undernutrition. Results: DB at the individual level is found in 19% of the adults, but only in 1% of the children. DB at the household level is relatively low (1–3%) when using wasting or underweight as indicators of child undernutrition, but much higher (13–17%) when using stunting or micronutrient deficiency as indicators. Conclusion: Various forms of DB problems exist in rural Kenya at household and individual levels. Prevalence rates depend on how exactly DB is defined and measured. The rise of overweight and obesity, even in rural areas, and their coexistence with different forms of undernutrition are challenges for food and nutrition policies.